Hadith as The Philosophical Foundation of Lifelong Education - Muhammad Rajiannor; Nuril Huda; Hairul Hudaya (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study presents an in-depth review of the concept of Life-Long Education within the framework of the Hadith (sayings and actions) of Prophet Muhammad ﷺ, emphasizing that this idea is not an imported concept but a theological obligation and a solid philosophical foundation within Islam. Although education is often misunderstood as a formal process that ceases upon graduation, the Hadith unequivocally establishes thalabul ‘ilmi (seeking knowledge) as fardhu 'ain (an individual obligation) whose execution transcends age limits, continuing persistently “from the cradle to the grave.” The research method used is a qualitative-descriptive literature review focusing on the thematic analysis of the Hadith, supported by relevant academic literature from the last ten years. The analysis is focused on the meaningful interpretation of key Ahadith (plural of Hadith) concerning thalabul ‘ilmi, tarbiyah (character development), and al-ilm an-nafi’ (beneficial knowledge). The findings of this study indicate that the Hadith provides a holistic framework that successfully integrates intellectual competence and moral integrity, where tarbiyah and the formation of insan kamil (the perfect human being) are the main objectives of the continuous education process.